Análisis de estabilidad de taludes submarinos por el método Shear Band Propagation (2020)
Slope stability analyses are common for infrastructure development on earth's surface and continental platforms worldwide. Slope instability occurs when acting stresses are greater than soil strength, which produces a mass movement that can affect both population and infrastructure when it occurs on earth's surface and, in submarine environments, mass movements affects submerged infrastructure and coastal population due to the possible occurrence of tsunamis. Landslides are more studied in the sub-aerial environment as they can be easily identifiable. However, landslides can also occur on submerged environments, this causes that more studies focusing on submerged slope stability should be performed to plan and protect submarine and coastal infrastructure like intercontinental internet network cables and off-shore oil platforms. With this aim, this study focuses in determining submerged slope stability using the Shear Band Propagation Method. This method was implemented and calibrated with the results registered previously by Puzrin et al. (2016) and based on the implementation made, a series of stability phase diagrams that can establish slope stability based on the submerged slope geomorphological properties was created. Geomorphological properties can be extracted from bathymetric information, which eases stability analyses in broad study areas.